Neutrophils: emerging perspectives on the pathogenesis of oral mucosal diseases - Chen, Yuhe; Mi, Qian; Jia, Fang; Meng, Wenxia (Frontiers in Cellular and Infection Microbiology, 2025)
Neutrophils, as the predominant effector cells of innate immunity and the first line of defense at the oral mucosal barrier, play pivotal yet complex roles in both immune defense and pathological damage within the unique oral environment. The oral mucosa, continuously exposed to physical, chemical, and dense microbial challenges, necessitates a dynamic and robust immune response. Recent evidence highlights that neutrophils are not merely transient defenders but key regulators whose functions are profoundly shaped by the specific milieu of the oral cavity, differing significantly from other mucosal sites. However, the precise mechanisms by which neutrophils contribute to the pathogenesis of various oral mucosal diseases (OMDs), beyond their established role in barrier defense, remain inadequately synthesized and understood. This article systematically reviews the mechanisms underpinning neutrophil-mediated immune defense in the oral mucosa and critically summarizes their documented involvement in major OMDs, including oral candidiasis, recurrent aphthous ulcer, Behçet’s disease, and oral potentially malignant disorders/cancer. By elucidating the unique interplay between oral environmental cues (microbiota, function, systemic factors) and neutrophil behavior, this review aims to provide novel insights into the immunopathogenesis of OMDs and inform future translational research targeting neutrophil function.